Long-term Correlations and Rare Events in Futures Volatility - Gong, Bosichan (2015)
This dissertation analyse the statistics of rare events in the futures market. We focus on the futures absolute return volatilities that are long-term correlated and show the eect of long-term memory on the return intervals of extreme events. The heuristic study has been investigated by some econophysics methods. The results show that the return intervals distribution contain scaling property and the scaling form is approach to a stretched expo- nential function. The stretching exponent is identical to the long-term correlation exponent . The long-term correlation has also been found among return intervals and the long-term correlated exponent is close to as well. This paper (Cizeau et al. 1997) veried results by the futures volatility.